2005
DOI: 10.1007/s00520-005-0859-7
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of feeding independence in end-stage cancer patients under palliative care—a prospective, uncontrolled study

Abstract: The prospective study showed for the first time that the provision of appropriate feeding supports could markedly enhance feeding independence in end-stage cancer patients receiving palliative care, which might improve activities of daily living and QOL, and minimize excessive disability. Furthermore, it merits cooperation among occupational therapists, caregivers, and ward staff to promote feeding independence in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 11 publications
1
24
0
2
Order By: Relevance
“…PT and OT services seek to enhance functional performance and greater independence in activities of daily living (ADLs) and thus enable people to live both independently and productively. Over the last two decades, PT and OT professions have continued to grow in China in response to the aging population, the increasing incidences of head and spinal cord injury, and epidemics such as AIDS and cancer [13,18]. At the same time rehabilitative professionals are being trained in TCM methods allowing patients to be treated with both modalities.…”
Section: Discussionmentioning
confidence: 98%
“…PT and OT services seek to enhance functional performance and greater independence in activities of daily living (ADLs) and thus enable people to live both independently and productively. Over the last two decades, PT and OT professions have continued to grow in China in response to the aging population, the increasing incidences of head and spinal cord injury, and epidemics such as AIDS and cancer [13,18]. At the same time rehabilitative professionals are being trained in TCM methods allowing patients to be treated with both modalities.…”
Section: Discussionmentioning
confidence: 98%
“…In the end-of-life and hospice setting, rehabilitation interventions have been shown to improve independence, reduce anxiety and depression, and improve fatigue, among other benefits [4952]. One randomized control trial compared hospice patients who received daily rehabilitation compared to usual care, and found that the rehabilitation group resulted in less unmet needs at the end of life in psychological, physical, activities of daily living, care and support, and pain domains.…”
Section: Introductionmentioning
confidence: 99%
“…The study found patients in the mental imagery programme improved more than the functional skills group and were more likely to transfer learned skills to other tasks. In a fourth, uncontrolled prospective study investigating the effectiveness of occupational therapy in improving eating in 36 in-patients with end-stage cancer, Lee et al (2005) found a significant improvement in eating independence over 1 week, which was maintained over 3 weeks. Assessment was completed using the Barthel Index.…”
Section: Occupational Therapists' Role In Reducing Nutritional Riskmentioning
confidence: 99%
“…Our primary Nicola Ann Plastow, Georgia Spiliotopoulou, Anita Atwal, and Mary Gilhooly concern is related to the validity and reliability of the tools used. Some of the studies developed their own measures, without any rigorous testing for validity and reliability (Kondo et al 1997, Lee et al 2005, Liu et al 2004. The validity of selecting items from existing scales, without considering if each item is a valid and reliable measure of the task of interest, is also questionable.…”
Section: Occupational Therapists' Role In Reducing Nutritional Riskmentioning
confidence: 99%